Misdiagnosis of Rectus Abdominis Abscess Owing to Delayed Contrast-Enhanced Computed Tomography - Yuichiro Nagase; Yukinori Harada (European Journal of Case Reports in Internal Medicine, 2021)
A 77-year-old man, who was on anticoagulation, presented with a painful lump on the right abdominal wall. Laboratory tests showed slight anaemia and elevated inflammatory markers. Abdominal plain computed tomography (CT) revealed a mass in the right rectus abdominis muscle. He was admitted with a diagnosis of primary rectus abdominis haematoma. However, on the next day, the diagnosis was corrected to primary rectus abdominis abscess, following contrast-enhanced CT of the abdomen. This case illustrates the importance of considering primary rectus abdominis abscess in patients with suspected primary rectus abdominis haematoma, and contrast should be used when performing CT.